Tillichian teleodynamics: An Examination of the Multidimensional Unity of Emergent Life - Pryor, Adam (Zygon, 2011)
Emergence theory has generated many significant new questions for dialogue between theology and science. My work will examine the models of one emergence theorist, Terrence Deacon, and consider the constructive potential of Tillich's multidimensional unity of life for responding to the theological ramifications of this account of emergence theory. Such a Tillich-inspired constructive process will rely upon Robert Russell's method of “Creative Mutual Interaction.” Building on the interactive quality of Russell's method, I will also begin to offer suggestions for how Tillich's theological themes might influence scientific research programs using Deacon's emergence theory by contributing to the process of defining life. Finally, I will conclude by identifying three facets of continued research that stem from this analysis, focusing primarily on its implications for theological anthropology and what it means to be in the image of God.